Situation Report: Baltic Area, 18 December 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. US Policy on Baltic States Draws Extraordinary Soviet Protests / by Dzintra Bungs Demonstration Held on Anniversary of October Revolution / by Toomas Ilves More Unrest: Ethnic Strife, Demonstrations, and a Wary Official Response / by Toomas Ilves Hydroelectric Power Station Project Discontinued / by Dzintra Bungs A Survey of the Demonstrations on November 18 / by Dzintra Bungs Latvian Poet on "National Rebirth of Internationalism" / by Dzintra Bungs A Forthright Discussion of Mobilization for Harvests / by Saulius Girnius New First Secretary of Lithuanian Communist Party / by Saulius Girnius